Non-linear associations of atherogenic index of plasma with prediabetes and type 2 diabetes mellitus among Chinese adults aged 45 years and above: a cross-sectional study from CHARLS - Jiang, Luqing; Li, Lei; Xu, Zichen; Tang, Yu; Zhai, Ying; Fu, Xia; Liu, Daoqin; Wu, Qiwen (Frontiers in Endocrinology, 2024)
Background: Dyslipidemia is strongly associated with the development of prediabetes and type 2 diabetes mellitus (T2DM). The atherogenic index of plasma (AIP), as a comprehensive index for assessing lipid metabolism, has received extensive attention from researchers in recent years. However, there are relatively few studies exploring the relationships between AIP and the risk of prediabetes and T2DM in the Chinese population. This study focuses on exploring the relationships of AIP with the risk of prediabetes and T2DM in the Chinese population. Methods: We conducted an analysis on the public data from the China Health and Retirement Longitudinal Study (CHARLS), involving a total of 12,060 participants aged 45 years and above in China. The study explored the relationships of AIP with prediabetes and T2DM risk through multivariate logistic regression, subgroup analysis, smooth curve fitting, and threshold effect analysis. Results: After adjusting for potential confounding factors, we observed positive associations between AIP and the risk of prediabetes (OR = 1.75, 95% CI: 1.49-2.06) and T2DM (OR = 2.91, 95% CI: 2.38-3.57). Participants with higher AIP levels demonstrated significantly elevated risk of prediabetes (OR = 1.52, 95% CI: 1.33-1.74) and T2DM (OR = 2.28, 95% CI: 1.92-2.71) compared to those with lower AIP levels. AIP showed consistent correlations with prediabetes and T2DM risk in different subgroups. The results showed the nonlinear relationships between AIP and risk of prediabetes and T2DM, with inflection points at 0.29 and -0.04, respectively. When AIP > 0.29, there was a positive association between AIP and the risk of prediabetes (OR = 2.24, 95% CI: 1.67-3.00, P < 0.0001). Similarly, when AIP > -0.04, AIP was positively associated with the risk of T2DM (OR = 3.33, 95% CI: 2.67-4.16, P < 0.0001). Conclusions: This study demonstrated non-linear positive associations of AIP with the risk of prediabetes and T2DM among participants ≥ 45 years of age in China.